Comparative Analysis of Religious Moderation and Inclusivity in SMAN 2 and MAN Tanjungpinang - Dewi, Ning Ratna Sinta; Fazal, Khairil (Program Studi Sosiologi Agama Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri Ar-Raniry, Banda Aceh, Indonesia, 2024)
Indonesia is comprised of diverse tribes, languages, and faiths. While this diversity enhances societal resilience, it also presents obstacles in terms of interreligious and cultural exchanges. The study aims to assess the comprehension and implementation of religious moderation among students at State High School 2 and Madrasah Aliyah State (MAN) Tanjungpinang. The study employs exploratory quantitative methodologies by gathering data using questionnaires that contain statements pertaining to interreligious and multiracial tolerance. The data obtained from the questionnaire is subjected to statistical analysis in order to determine the distribution of replies and to discover any significant differences between the two groups of pupils. Furthermore, in-depth interviews were carried out to offer supplementary background. The findings revealed substantial disparities in students' comprehension and perspectives regarding religious moderation. MAN students exhibit a greater inclination towards inclusivity and acceptance of diversity compared to SMAN 2 pupils. The study determined that the educational setting and the school atmosphere had a significant impact on influencing students' views and behaviors towards ethnic and religious diversity.